PJMHS 2021
DOI: 10.53350/pjmhs211592460
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Suboptimal Health Status among Young Adults and Its Association with Their Demographic Factors

Abstract: Objective: To assess the suboptimal health status among young adults and its association with their demographic factors visiting institute of dentistry CMH, Lahore Design of the Study: It was a cross-sectional study. Study Settings: This study was carried out at Outpatient Department of Dentistry Combined Military Hospital, Lahore from August 2020 to January 2021. Material and Methods: A cross-sectional study was carried out with sample of 384 young adults visiting institute of dentistry CMH, Lahore. Suboptima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[5][6][7][8][9] Internationally, studies have been conducted on the SHS of pregnant women, young people and university students. [10][11][12] In all the mentioned studies, the SHMSV1.0 scale is the most commonly used instrument to measure SHS and the influencing factors are various for the different characteristics of different occupations, however, variables like exercising frequency, diet condition and eating condition are frequently mentioned in studies. Besides, studies have also shown that subhealth is significantly associated with the shortening of chromosomal telomeres, which can be used as a predictor of physiological aging.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Internationally, studies have been conducted on the SHS of pregnant women, young people and university students. [10][11][12] In all the mentioned studies, the SHMSV1.0 scale is the most commonly used instrument to measure SHS and the influencing factors are various for the different characteristics of different occupations, however, variables like exercising frequency, diet condition and eating condition are frequently mentioned in studies. Besides, studies have also shown that subhealth is significantly associated with the shortening of chromosomal telomeres, which can be used as a predictor of physiological aging.…”
Section: Introductionmentioning
confidence: 99%